Relationship between Anti-Wrinkle Property of Cotton Fabrics and Crosslinking Properties of Glycosyl Polyaldehydes and Polyuronic Acids Finishing Agents: A Molecular Simulation Study - Jiangfei Lou (MDPI AG, 2021)
In this paper, monosaccharide (glucose and fructose), disaccharide (sucrose and trehalose), trisaccharide (raffinose) and tetrasaccharide (stachyose) were selected as the research objects and the glycosyl polyaldehydes and glycosyl polyuronic acid anti-wrinkle finishing agents were prepared via selective oxidation. The anti-wrinkle properties of their finished fabrics were analyzed, the molecular radius, the number of reactive groups, the number of reaction sites and the number of rotatable bonds of the finishing agent were calculated to evaluate its diffusion rate and crosslinking characteristics inside the cellulose. Through molecular simulation, the number of possible conformations of the anti-wrinkle finishing agent with the single cross-linked state was calculated, and the distance between different cross-linking points was measured, and the relationship between the effective cross-linking radius and the anti-wrinkle performance was studied. The results showed that trehalose polyaldehydes, raffinose polyaldehydes, trehalose polyuronic acid, and raffinose polyuronic acid finished fabrics had an excellent anti-wrinkle property, the strength retention rates of the fabrics were all above 68%, and the whiteness index was above 70. The smaller the molecular radius was, the easier the finishing agent was to diffuse into the cellulose. The most suitable crosslinking radius of glycosyl finishing agent was 3.5–6.0 Å.